A non-clinical comparative study of IL-23 antibodies in psoriasis. Issue 1 (1st January 2021) - Zhou, Li; Wang, Yibing; Wan, Qi; Wu, Fei; Barbon, Jeffrey; Dunstan, Robert; Gauld, Stephen; Konrad, Mark; Leys, Laura; McCarthy, Richard; Namovic, Marian; Nelson, Christine; et al.
ABSTRACT: Four antibodies that inhibit interleukin (IL)-23 are approved for the treatment of moderate-to-severe plaque psoriasis. Here, we present non-clinical data comparing ustekinumab, guselkumab, tildrakizumab and risankizumab with regard to thermostability, IL-23 binding affinity, inhibitory-binding mode, in vitro potency and in vivo efficacy. Risankizumab and guselkumab exhibited 5-fold higher affinity for IL-23 and showed more potent inhibition of IL-23 signaling than ustekinumab and tildrakizumab. Risankizumab and guselkumab completely blocked the binding of IL-23 to IL-23Rα as expected, whereas tildrakizumab did not. In vitro, risankizumab and guselkumab blocked the terminal differentiation of TH 17 cells in a similar manner, while tildrakizumab had minimal impact on TH 17 differentiation. In a human IL-23-induced ear-swelling mouse model, risankizumab and guselkumab were more effective than ustekinumab and tildrakizumab at reducing IL-17, IL-22, and keratinocyte gene expression. Our results indicate that the four clinically approved antibodies targeting IL-23 differ in affinity and binding epitope. These attributes contribute to differences in in vitro potency, receptor interaction inhibition mode and in vivo efficacy in preclinical studies as described in this report, and similarly may affect the clinical performance of these drugs.